Pregnancy incidence and associated factors among HIV-infected female adolescents in HIV care in urban Côte d'Ivoire, 2009-2013 - Shino Arikawa; Tanoh Eboua; Kouadio Kouakou; Marie-Sylvie N'Gbeche; Madeleine Amorissani-Folquet; Corinne Moh; Ursula Belinda Amoussou-Bouah; Patrick Ahuatchi Coffie; Renaud Becquet; Valériane Leroy (Taylor & Francis Group, 2016)
Objective: Adolescents living with HIV are sexually active and engaged in risky sexual behaviors. Knowledge on how and to what extent adolescents in HIV care are affected by pregnancy is needed so as to adopt better preventive services. We estimated 4-year pregnancy incidence and correlates among HIV-infected female adolescents in HIV care in urban Côte d'Ivoire. Design: We conducted retrospective analysis of a pediatric prospective cohort of the International epidemiological Databases to Evaluate AIDS (IeDEA) West Africa Collaboration. Female patients with confirmed HIV infection aged 10-19 years, having at least one clinical visit in 2009 to health facilities participating in the pediatric IeDEA West African cohort in Abidjan, Côte d'Ivoire, were included. Data on incident pregnancies were obtained through medical records and interviews with health professionals. Pregnancy incidence rate was estimated per 100 person-years (PY). Poisson regression models were used to identify factors associated with the first pregnancy and provided incidence rate ratios (IRR) with 95% confidence intervals (CI). Results: In 2009, 266 female adolescents were included, with a median age of 12.8 years (interquartile range, IQR: 10.0-15.0), CD4 cell counts of 506 cells/mm3 (IQR: 302-737), and 80% on antiretroviral treatment. At the 48th month, 17 new pregnancies were reported after 938 PY of follow-up: 13 girls had one pregnancy while 2 had two pregnancies. Overall incidence rate of pregnancy was 1.8/100 PY (95% CI: 1.1-2.9). High incidence was observed among those aged 15-19 years: 3.6/100 PY (95% CI: 2.2-5.9). Role of maternal death in the risk of pregnancy was at the limit of statistical significance (adjusted IRR: 3.1, 95% CI: 0.9-11.0; ref. non-maternal orphans). Conclusions: Incidence of pregnancy among HIV-infected adolescents in care aged 15-19 years reached a level observed in adult cohorts in Sub-Saharan Africa. Health personnel in pediatric care have to intensify their efforts to provide more realistic and age-adapted reproductive health services to meet the needs of adolescent patients already confronting issues of sexuality. Vulnerability of maternal orphans merits further investigation.